The Right to Information Act 2005 a handbook - Naib, Sudhir (New Delhi ; Oxford : Oxford University Press, 2011)
Separated into 8 detailed chapters, this handbook provides a comprehensive and detailed introduction to the Right to Information Act 2005 and its implementation. It is one of the most remarkable pieces of world legislation which, for the first time, empowers Indian citizens to access information in the possession of public officials and authorities.
Includes bibliographical references and index.
Description based on print version record.
Keywords: India; Freedom of information -- India